Strategic Orientation, Innovation, and Female Leadership in Sharia SME Performance - Rosadi, M Imron; Budi Helpiastuti, Selfi; Kuswandi, Aos (Inovasi Analisis Data, 2025)
Objective: The objective of this study is to establish how female leadership and access to finance influence performance in Sharia-compliant SMEs.Methods: A cross-sectional survey design was employed. The data gathered were tested to examine the direct impact of leadership competency, gender, strategic orientation, and innovation capacity on performance and access to finance with a mediator in multiple regression analysis and mediation analysis t-test.Results: These results support the strategic orientation, innovation capability, and leadership competence as significant positive predictors of SME performance. In addition, when female leadership is considered, a weak but significant positive influence is confirmed. Access to finance was importantly both a direct determinant as well as an important mediator, through which the impact of all explanatory variables influences performance.Novelty: This study makes a novel contribution by combining female leadership in a strategic capability framework and empirically examining access to finance as the key mediating role in an ethical business context. It also fills an important void in terms of the interaction between gender, internal resources, and financial constraints.Research Implication: There is a validated framework for entrepreneurs to draw upon leadership and strategic resources. It provides evidence-based knowledge to policymakers and financial intermediaries to create enabling ecosystems that facilitate capital access, in particular for women-owned and ethically driven SMEs, contributing to inclusive and sustainable economic growth.